Experiências de escrita literária em sala de aula: criando fanfics a partir dos contos de Conceição Evaristo - Marques, Jucinalva dos Santos (2024)
One of the most prominent challenges in Elementary Education (Ensino Fundamental Anos Finais) has always been getting students to enjoy reading and writing. Conscious of this difficulty, this study examines the practice of literary mediation and creative writing, specifically through the fanfic genre, to develop students' reading and authorial writing skills in the context of Brazilian Law 10639/03 which requires people to teach aspects of Afro Brazilian’s literary topics. The research happened with a 9th-grade class at José Osete de Carvalho Municipal Elementary School in Cardeal da Silva, Bahia State. The study used action research methodology and focused resources from multimodal texts and collaborative writing on digital networks to engage students in reading and writing from contemporary black women's writings. The goal contributed to deconstructing ethnic-racial prejudice and enhanced writing as a tool for youth protagonism in social insertion. The study introduced a didactic sequence (Dolz and Scheneuwly, 2004) of five modules and created a pedagogical notebook as a final product, which can serve as a model for language and literature teachers to develop similar activities in their classes. The analysis used studies from various authors focused on learning and reading strategies from Solé (1998), Marcuschi (2008) and Rojo (2004) writings. Specifically, Vargas (2015) explores the use of fanfiction drawing on the work. Also, authors such as Cândido (2011) and Compangnon (1999) supported the analyses of the humanizing power of literature. The study even referenced black female writers like Evaristo (2016), Kilomba (2020), and Oliveira (2020) to explore associated themes. The student's participation in fanfic production classes proved to be instrumental in improving their perception of reading and text production, advancing and stimulating collaborative work.